FEASIBILITY STUDY OF TOUR GUIDE MANAGEMENT BUSINESS - Ahmad Kurniawan; Debby Rusmiati; Dewi Turgarini; Caria Ningsih (Sekolah Tinggi Pariwisata Mataram, 2022)
The phenomenon in the field is seen by many Indonesian tour guides who are now increasingly showing a decrease in the number of jobs that can be obtained. Not to mention, due to the ongoing pandemic, this has caused a lack of enthusiasm for the tour guides who have long been involved in revitalizing the tourism sector today. Based on the findings, it was found that 80% of tour guides do not have permanent jobs in guiding tours in the field, even though they are licensed and certified tour guides, so there needs to be management that accommodates Indonesian tour guides to be able to get a more definite job. Seeing this phenomenon, it is necessary to have management that accommodates the tour guides, thus providing the ability of researchers to review this research related to the feasibility study of tour guide management business on CV. PGM Organizer. With the aim of knowing how feasible this business is to be run so that it can be known to the maximum and according to the needs of the company. Through descriptive qualitative research methods using purposive sampling through data collection techniques by observation, interviews, and documentation. That way it can be seen that the results in sales made by the management of this tour guide are successful and get good profits. Therefore, to run the wheels of the economy in the world of tour guides, it turns out that there is a need for management that can accommodate it so that the activists of the travel industry can feel the same way.